Design of the vertical trajectory for arrival and departure routes at Prague airport - Hrdlička, Šimon; Hrdlička, Šimon; Schmidt, Stanley; Pilmannová, Terézia; Pilmannová, Terézia (České vysoké učení technické v Praze, 2025)
Numerous operational methods and related research focus on the efficient use of controlled airspace and thus on the management of its capacity. During the optimisation processes, various legislative limitations or technological constraints might appear. As the aviation industry continues to evolve, it occasionally happens that one of these pillars lags behind the other. This research focuses on a relatively underexplored aspect of using vertical profiles of air traffic service routes within the TMA Praha to optimise traffic flow in terms of flight efficiency and environmental impact.Virtual points, defining the aircraft’s vertical position limits along the given route, were computed to establish a vertical profile on already published standard departure or arrival routes. These points define the aircraft’s vertical position limits along the given route. Along with the proposal of a vertical profile, newly designed arrival and departure routes were implemented into the air traffic control simulation tool Escape Light and validated simultaneously within X-Plane simulator. Simulation studies conducted in these environments demonstrated significant fuel savings, averaging 13.2 %, with even greater savings observed in the Boeing 737-800, exceeding 25 %. These results confirm that applying vertical profiles positively impacts fuel consumption and contributes to more environmentally friendly operations.